2022
DOI: 10.3389/fpubh.2022.900293
|View full text |Cite
|
Sign up to set email alerts
|

Health Professionals' Attitude Toward the Use of Social Media for COVID-19 Related Information in Northwest Ethiopia: A Cross-Sectional Study

Abstract: BackgroundSocial media platform is one way to share online information regarding pandemic prevention. However, there is no study regarding the attitude of health professionals toward social media use for the COVID-19-related information. This study aimed to assess health professionals' attitudes toward using social media for COVID-19-related information.MethodsAn institution-based cross-sectional study was conducted among 355 health professionals in Bahir Dar city public health centers, Northwest Ethiopia. A p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 35 publications
2
6
0
Order By: Relevance
“…This suggests that health providers needed access to the EMR guidelines to promote the usage of EMR systems. Substantial evidence from various places supports this justification [28][29][30]. Our analysis also revealed that receiving management assistance has a significant association with the use of EMR systems.…”
Section: Comparison With Prior Worksupporting
confidence: 66%
See 1 more Smart Citation
“…This suggests that health providers needed access to the EMR guidelines to promote the usage of EMR systems. Substantial evidence from various places supports this justification [28][29][30]. Our analysis also revealed that receiving management assistance has a significant association with the use of EMR systems.…”
Section: Comparison With Prior Worksupporting
confidence: 66%
“…Previous investigations have also supported these findings [2,21]. This might be because younger medical professionals are more open to adopting new technologies and have a better comprehension of information and communications technology than their older counterparts [28][29][30]. This implied that special attention should be paid to older health care professionals to boost the acceptance of the new health information technology.…”
Section: Comparison With Prior Workmentioning
confidence: 68%
“…In contrast, the final score of one (not yet prepared) was categorised as ‘not ready to implement an EMR system’. 30 31 …”
Section: Methodsmentioning
confidence: 99%
“…The item scores for each organisational readiness component were added and divided by the number of items to create a composite variable ranging from scores 1 to 3 for the data analysis 28–30. As a result, two or more final scores (highly prepared, moderately prepared) were labelled as ‘Ready to implement an EMR system’.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation